2017
DOI: 10.1038/ncomms15075
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a heterotrimeric archaeal DNA polymerase holoenzyme

Abstract: Since their initial characterization over 30 years ago, it has been believed that the archaeal B-family DNA polymerases are single-subunit enzymes. This contrasts with the multi-subunit B-family replicative polymerases of eukaryotes. Here we reveal that the highly studied PolB1 from Sulfolobus solfataricus exists as a heterotrimeric complex in cell extracts. Two small subunits, PBP1 and PBP2, associate with distinct surfaces of the larger catalytic subunit and influence the enzymatic properties of the DNA poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…Recent gene deletion studies on hyperthermophylic Euryarchaea have demonstrated that only PolD is required for viability, suggesting that PolD is solely responsible for DNA replication, whereas PolB may be required for DNA repair 21,22,51 . It is noteworthy that the situation is different in Crenarchaea, which do not possess PolD 52 . Due to the multiple biological reactions required during DNA replication, PolD must be able to switch from one replication factor to another in a spatially and temporally regulated process.…”
Section: Discussionmentioning
confidence: 94%
“…Recent gene deletion studies on hyperthermophylic Euryarchaea have demonstrated that only PolD is required for viability, suggesting that PolD is solely responsible for DNA replication, whereas PolB may be required for DNA repair 21,22,51 . It is noteworthy that the situation is different in Crenarchaea, which do not possess PolD 52 . Due to the multiple biological reactions required during DNA replication, PolD must be able to switch from one replication factor to another in a spatially and temporally regulated process.…”
Section: Discussionmentioning
confidence: 94%
“…Sequence analysis indicated that the Ca. N. cavascurensis homolog belongs to the polB1 group present exclusively in the TACK superphylum and shown recently by Yan and colleagues to be responsible for both leading and lagging strand synthesis in the crenarchaeon Sulfolobus solfataricus ( Yan et al, 2017 ). However, the activity of Sulfolobus solfataricus PolB1 is dependent on the presence and binding of two additional proteins, PBP1 and PBP2, mitigating the strand-displacement activity during lagging strand synthesis and enhancing DNA synthesis and thermal stability of the holoenzyme, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Each DNA polymerase may consist of a single polypeptide chain as is observed for X and Y family members (35, 37), or along with 1–3 accessary subunits as many A- and B-family members (4147). Telomerase (RT family) is composed of a catalytic subunit (TERT), RNA (TER) and multiple other protein subunits (29, 48).…”
Section: Dna Polymerases For Replication and Repairmentioning
confidence: 99%